Animal Welfare and Resistance to Disease: Interaction of Affective States and the Immune System - Düpjan, Sandra; Dawkins, Marian Stamp (Frontiers in Veterinary Science, 2022)
Good management and improved standards of animal welfare are discussed as important ways of reducing the risk of infection in farm animals without medication. Increasing evidence from both humans and non-human animals suggests that environments that promote well-being over stress and positive over negative emotions can reduce susceptibility to disease and/or lead to milder symptoms. We point out however, that the relationship between welfare, immunity and disease is highly complex and we caution against claiming more than the current evidence shows. The accumulating but sometimes equivocal evidence of close links between brain, gut microbiome, immunity and welfare are discussed in the context of the known links between mental and physical health in humans. This evidence not only provides empirical support for the importance of good welfare as preventative medicine in animals but also indicates a variety of mechanisms by which good welfare can directly influence disease resistance. Finally, we outline what still needs to be done to explore the potential preventative effects of good welfare.